HUBUNGAN GETARAN LENGAN-TANGAN DEGAN HAND ARM VIBRATION SYNDROME PADA PEKERJA BAGIAN PEMOTONGAN DAN PENGHALUSAN PENGRAJIN GITAR DI SUKOHARJO - Afdim Febryandra Mastha; Siswi Jayanti; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Hand Arm Vibration Syndrome is a syndrome that is caused due to operate tools that vibrate continuously which may affect the symptoms of vascular, neurological, and musculoskeletal. The aim of research to determine the relationship of hand-arm vibration with hand arm vibration syndrome in workers cutting and rarefaction part in Sukoharjo guitar craftsmen. Kind of explanatory research using quantitative approach with cross sectional study design. The dependent variable Hand Arm Vibration Syndrome research and measurement using the classification of Stockholm, the independent variables of this research are large and long exposure to hand-arm vibration measurements using large vibration and vibration meters long exposure using a questionnaire. Population and sample in the study were all workers in the process of cutting and rarefaction the guitar craftsman Hamlet Village Kembangan Mancasan Sukoharjo, at 11 Home guitar craftsman industry amounted to a total of 36 workers. Analysis of data using univariate and bivariate analysis with Spearman Rank test. Univariate results of the average length of exposure to hand-arm vibration is 8.53 hours, an average of hand-arm vibration cutting process and refining is 51.03 m / s2, and the stage of HAVS (vascular symptoms + sensorineural) process of cutting and rarefaction HAVS 20 respondents did not experience and the experience of Hand Arm Vibration Syndrome amounted to 16 respondents. Results of bivariate analysis showed that there is a great relationship-hand arm vibration exposure to Hand Arm Vibration Syndrome (p-value 0.001) and there is long-standing relationship-hand arm vibration exposure to Hand Arm Vibration Syndrome (p-value 0.001). The conclusion of this study is that there is a great relationship and long exposure to hand-arm vibration with Hand Arm Vibration Syndrome. Industry research is conducted also suggest owners must provide rotation on worker cutting process and rarefaction.